Food and Eating in the Bronte Novels - Lucraft, Fiona (Petits Propos Culinaires, 1999)
This paper, an important reference for anyone working on food in English literature, was contributed to the Oxford Symposium on Food, 1998. It is a study of the depiction and purpose of food (and drink) in the novels of Charlotte, Anne and Emily Bronte.